2019
DOI: 10.1111/cobi.13328
|View full text |Cite
|
Sign up to set email alerts
|

Using individual‐based movement information to identify spatial conservation priorities for mobile species

Abstract: The optimal design of reserve networks and fisheries closures depends on species occurrence information and knowledge of how anthropogenic impacts interact with the species concerned. However, challenges in surveying mobile and cryptic species over adequate spatial and temporal scales can mask the importance of particular habitats, leading to uncertainty about which areas to protect to optimize conservation efforts. We investigated how telemetry‐derived locations can help guide the scale and timing of fisherie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…Large‐scale seasonal migrations are common among euryhaline elasmobranchs, where these highly mobile predators provide broad and important cross‐biome trophic linkages between tropical freshwater and coastal ecosystems (Every et al., 2017; Matich & Heithaus, 2014). However, moving downstream can also bring potential costs for immature sharks, such as an elevated predation risk (Heupel & Simpfendorfer, 2011), increased resource competition from other marine species (Kinney et al., 2011; Yick et al., 2011) and potential interactions with commercial fisheries (Dwyer et al., 2019; Field et al., 2013). We demonstrated that individuals of both species limited their time in downstream estuarine habitats to only those months when salinities in upstream regions were substantially reduced as a consequence of seasonal increases in freshwater inflow.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Large‐scale seasonal migrations are common among euryhaline elasmobranchs, where these highly mobile predators provide broad and important cross‐biome trophic linkages between tropical freshwater and coastal ecosystems (Every et al., 2017; Matich & Heithaus, 2014). However, moving downstream can also bring potential costs for immature sharks, such as an elevated predation risk (Heupel & Simpfendorfer, 2011), increased resource competition from other marine species (Kinney et al., 2011; Yick et al., 2011) and potential interactions with commercial fisheries (Dwyer et al., 2019; Field et al., 2013). We demonstrated that individuals of both species limited their time in downstream estuarine habitats to only those months when salinities in upstream regions were substantially reduced as a consequence of seasonal increases in freshwater inflow.…”
Section: Discussionmentioning
confidence: 99%
“…By linking physiological approaches with observations of how animal movements and local environmental parameters change in space and time, it may be possible to reveal mechanistic insights into how environmental variation drives patterns of habitat use, river connectivity and community structure in elasmobranch nursery habitats. Furthermore, having a species‐specific understanding of habitat preferences, ecosystem drivers of animal movements and physiological tolerances can help resource managers identify critical habitat, develop effective by‐catch reduction schemes and forecast population effects caused by natural and anthropogenic changes to the local environment (Dwyer et al., 2019; Horodysky et al., 2015; Whitlock et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…, Dwyer et al. ). For wide‐ranging and long‐lived species, the need to observe movements of individuals at biologically relevant spatial and temporal scales increases this difficulty even further (Nelson et al.…”
Section: Introductionmentioning
confidence: 99%
“…Restoration and conservation program guidelines that incorporate behavioral diversity of habitat use can increase resiliency of populations to stochastic environmental events and increase long-term persistence of at-risk species (Alagona et al 2012, Waldman et al 2016. However, developing guidelines to conserve behavioral diversity is difficult because variation at the individual level is infrequently studied despite recognition that habitat use of mobile species is unlikely to fit a generalist pattern (Fodrie et al 2015, Dwyer et al 2019. For wide-ranging and long-lived species, the need to observe movements of individuals at biologically relevant spatial and temporal scales increases this difficulty even further (Nelson et al 2013).…”
Section: Introductionmentioning
confidence: 99%